Transforming growth factor beta inhibits formation of osteoclast-like cells in long-term human marrow cultures. - Chenu, C (1988)
Transforming growth factor beta (TGF-beta), a polypeptide present in abundant amounts in bone matrix, was examined for its effects on osteoclast formation by using a human bone marrow culture system in which multinucleated cells (MNCs) with osteoclast characteristics form. TGF-beta strongly inhibited MNC formation at concentrations as low as 1 ng/ml. TGF-beta also completely suppressed the effects of osteotropic factors known to stimulate MNC formation. The inhibitory effect of TGF-beta on osteoclast-like cell formation was more pronounced during the first week of culture, which corresponds to the period of proliferation of mononuclear osteoclast precursors. To examine whether the inhibitory effects of TGF-beta on MNC formation could be due to inhibition of the granulocyte/macrophage progenitor cell [colony-forming unit granulocyte/macrophage (CFU-GM)], the probable precursor for MNC, we tested the effects of TGF-beta on CFU-GM formation in presence of a source of colony-stimulating factor. Unexpectedly, TGF-beta at concentrations (0.1-1 ng/ml) that were inhibitory for MNC formation enhanced day 7 CFU-GM colony formation. This increase in CFU-GM colony formation seen in cultures containing TGF-beta resulted from significantly more granulocytic colonies being formed in the cultures, suggesting that TGF-beta may induce CFU-GM to differentiate preferentially to cells of the granulocytic lineage. Differentiation of CFU-GM to granulocytes rather than osteoclast precursors in response to TGF-beta would result in inhibition of MNC formation by depleting the precursor pool for MNC. These data suggest that inhibition of osteoclast-like cell formation by TGF-beta may be an important mechanism of control of local bone resorption.